Laboratory manual in forensic ballistics - Revisa, William A.; Magbojos, Roberto R.; Cartin, Rowela G. (Quezon City : Wisemans Books Trading, Inc., 2021)
"The goals of the lessons are to allow the students of the criminology program to become familiar with the principles, techniques and methodologies used by forensic specialist in firearm identification and accomplishing forensic ballistics report."
Includes appendices.
English text.
Keywords: Forensic ballistics -- Laboratory manuals